Organizational and occupational psychology: practice and use of assessment instruments and psychological testing - Elias, Patrícia Rodrigues; Silveira, Kátia Simone da Silva (Disciplinarum Scientia | Saúde, 2024)
Occupational and Organizational Psychology (OOP) has gone through changes over the years, therefore, understanding its historical concept and associating it to the contemporary processes is of paramount importance, especially regarding the use of Assessment Instruments and Psychological Testing as a mechanism that contributes to the performance of psychologists in the organizations. Thus, the objective of this article was to understand the work of Occupation and Organizational Psychologists while managing Psychological Assessments and using Psychological Testing, emphasizing their importance in the business organization. To develop this work, a bibliographic, qualitative narrative review was used, based on the LILACS, MedLine, and Psychology Index databases, through BVS and Sciello, in addition to books for conceptual support. As a result, 14 articles were obtained, duly evaluated by Minayo’s content analysis (2012). These data revealed that currently the importance of Occupational and Organizational Psychologists has been evident, since on average 30% of psychologists are taking up space in organizations, working in the Human Resources sector, a fact that points to an evolution of the profession and shows the importance of being anchored in both theory and practice. Considering their performance, the use of Psychological Assessment Instruments and Psychological Testing provides support to the professional in order to validate the Psychologists’ hypotheses, interpretations and perceptions, thus bringing responsible and reliable results to the organizations. Based on what was analyzed, it can be concluded that, to keep up with the changes in the modern world, it is necessary to understand the historical evolution of Occupational and Organizational Psychology (OOP) in order to relate it to social, economic and technological changes in the work environment. To this end, the work of Psychology professionals within business organizations must be supported by innovative tools that contribute to their performance, considering that these instruments support and assist the work of organizational psychologists by increasing its effectiveness and reliability through indicators that assess the interventions carried out.